The Effect of Therapeutic Play on Children's Anxiety in the Inpatient Room at the Dr. Rom. Djoelham Binjai - Domaria; Ardianto; Aldiansyah; Nurul Pratiwi; Selvi Aulia; Selvi Andaresta (Science Midwifery, 2020)
Children are unique individuals and not miniature adults. Children are also not a parent's property or wealth that can be assessed socio-economically, but the future of the nation who is entitled to individual health services and is still dependent on adults and their environment, meaning that they need an environment that can facilitate them in meeting their basic needs and for independent learning. . The effects of treatment experienced by children when seeking treatment at health care facilities need attention and problem solving so that when undergoing treatment a child knows and is cooperative in dealing with problems that occur during the treatment. Therapeutic play is believed to be able to eliminate boundaries, internal barriers, anxiety, frustration and have emotional problems with the aim of changing children's inappropriate behavior into expected behavior and children who are often invited to play will be more cooperative and easy to work with when undergoing treatment. Research Objectives To determine the effect of therapeutic play on children's anxiety in the inpatient ward of the Dr. RM. Djoelham Binjai and to determine the effect of therapeutic play on children's anxiety in the inpatient room of the Dr. Regional General Hospital. RM. Djoelham Binjai Year 2020. The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 1, the results are p.value = 0.000 at df = 1 where sig < (0.000 < 0 0.05), it can be seen that there is a therapeutic effect of play on children's anxiety in the inpatient room at the Dr. RM. Djoelham Binjai 2020.